2008
DOI: 10.1124/jpet.107.135046
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase-Catalyzed Transamidation: A Novel Mechanism for Rac1 Activation by 5-Hydroxytryptamine2AReceptor Stimulation

Abstract: Transglutaminase (TGase)-induced activation of small G proteins via 5-hydroxytryptamine (HT) 2A receptor signaling leads to platelet aggregation (Cell 115:851-862, 2003). We hypothesize that stimulation of 5-HT 2A receptors in neurons activates TGase, resulting in transamidation of serotonin to a small G protein, Rac1, thereby constitutively activating Rac1. Using immunoprecipitation and immunoblotting, we show that, in rat cortical cell line A1A1v, serotonin increases TGase-catalyzed transamidation of Rac1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 44 publications
1
95
1
Order By: Relevance
“…Examples in the literature include muscarinic receptor-mediated increases in TG2 activity in SH-SY5Y cells (Zhang et al, 1998) and 5-HT2A receptor-mediated transamidation (TG-catalyzed) of the small G-protein Rac1 in the rat cortical cell line A1A1v (Dai et al, 2008). The study by Zhang et al (1998) measured in situ TG2 activity (polyamine incorporation) triggered by the non-selective muscarinic agonist carbachol, whereas, Dai et al (2008) reported TG2 catalysed incorporation of 5-hydroxytryptamine into Rac1. 5-HT2A receptor-mediated incorporation of 5-HT into the small GTPases RhoA and Rab4 has also been observed in platelets (Walther et al, 2003).…”
Section: In Vitro Modulation Of Tg2 Transamidation Activity By the Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Examples in the literature include muscarinic receptor-mediated increases in TG2 activity in SH-SY5Y cells (Zhang et al, 1998) and 5-HT2A receptor-mediated transamidation (TG-catalyzed) of the small G-protein Rac1 in the rat cortical cell line A1A1v (Dai et al, 2008). The study by Zhang et al (1998) measured in situ TG2 activity (polyamine incorporation) triggered by the non-selective muscarinic agonist carbachol, whereas, Dai et al (2008) reported TG2 catalysed incorporation of 5-hydroxytryptamine into Rac1. 5-HT2A receptor-mediated incorporation of 5-HT into the small GTPases RhoA and Rab4 has also been observed in platelets (Walther et al, 2003).…”
Section: In Vitro Modulation Of Tg2 Transamidation Activity By the Pamentioning
confidence: 99%
“…However, the regulation of intracellular TG2 following stimulation of GPCRs is not well understood. Examples include muscarinic receptor-mediated increases in TG2 activity in SH-SY5Y cells (Zhang et al, 1998), 5-HT2A receptor-mediated transamidation of Rac1 in the rat A1A1v cortical cell line (Dai et al, 2008) and A1 adenosine receptor-mediated increases in TG2 transamidase activity in rat H9c2 cardiomyoblasts (Vyas et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Examples in the literature include muscarinic receptor-mediated increases in TG2 activity in SH-SY5Y cells [38] and 5-HT2A receptor mediated transamidation (TG-catalyzed) of the small G-protein Rac1 in the rat A1A1v cells [39].…”
Section: In Vitro Modulation Of Tg2 By the A1 Adenosine Receptormentioning
confidence: 99%
“…Zhang et al, [38] measured in situ TG2 activity (polyamine incorporation) triggered by the muscarinic agonist carbachol, whereas Dai et al, [39] reported TG2 catalysed incorporation of 5-hydroxytryptamine into Rac1. 5-HT2A receptor-mediated incorporation of 5-HT into the small GTPases RhoA and Rab4 was also observed in platelets [40].…”
Section: In Vitro Modulation Of Tg2 By the A1 Adenosine Receptormentioning
confidence: 99%
“…These results are in accordance with previous findings implicating 5-HT in the activation of transglutaminases. It has been demonstrated that 5-HT activation of 5-HT 2A receptors increases transglutaminase activity in the rat cortical cell line A1A1v (11). In rat aortic smooth muscle cells, a 10-min exposure to 5-HT induces activation of RhoA, via 5-HT 1B/1D receptors in a transglutaminase-dependent manner.…”
Section: ϫ4mentioning
confidence: 99%